Arts and Culture for Older People in Singapore: An Annotated Bibliography - Yuen, Belinda (SpringerBriefs in Aging,, 2018)
This book combines in a single volume numerous studies concerning the use of arts and culture to enhance quality of life, health and wellbeing among older people, especially in Singapore. The bibliography covers not only research conducted in Singapore (both published and grey literature), but also a global body of work encompassing the Asia-Pacific region, Europe and North America. In addition to the annotated bibliography, the opening chapter introduces the current state of policy, practice and research on arts and culture for older people in Singapore. The book offers a valuable point of reference for all readers interested in the use of artistic and cultural development as creative and non-pharmacological approaches to providing support throughout the ageing process. It will be particularly useful for anyone interested in research advances in participatory arts therapies and recreational activities for older individuals.